A new species of Andean golden poison frog (Andinobates, Dendrobatidae) from the Eastern Andes of Colombia - Chaves-Portilla, Giovanni A.; Salazar, Erika Nathalia; Gil-Acero, José; Dorado-Correa, Adriana; Márquez, Roberto; Rueda-Almonacid, José Vicente; Amézquita, Adolfo (Zootaxa, 2021)
A new species of Andinobates (Dendrobatidae) is described from the East Andes of Colombia, just 37 km away from the Colombian capital, Bogotá. Andinobates supata sp. nov., represents the second known species of yellow Andinobates, and can be distinguished from the other, Andinobates tolimensis, by an unique combination of ventral and dorsal color patterns. Our phylogenetic analyses, based on ≈ 1120 bp from two mitochondrial markers (16S rRNA and cytochrome b) showed that this new taxon is sister to a clade formed by A. cassidyhornae, A. bombetes, A. opisthomelas, A. tolimensis and A. virolinensis. The new species appears to be restricted to a handful of small forest fragments (<10 ha) distributed in no more than 5 km2, between 1800–2000 m elevation, where the human activity is high. In addition, more than 90% of the original forest has been logged at the type locality, and its watersheds receive considerable agrochemical discharges. Altogether, the evidence suggests that this new species should be listed as Critically Endangered and should receive immediate attention regarding basic research and urgent conservation measures.